Ensuring the safety of students in pesantren: A study on the ministry of religious affairs' role in handling violence cases - Rahmawati, Dini; Rohman, Ahmad Fatkhur (Pusat Studi Gender dan Anak, 2025)
Cases of violence within pesantren (Islamic boarding schools) continue to occur. According to data from the Indonesian Teachers Union Federation (FSGI), 101 children were recorded as victims of sexual violence in schools between January and August 2024—all within educational institutions, across eight different cases. Of these, three cases occurred in boarding schools, while the other five took place in institutions under the supervision of the Ministry of Religious Affairs. This qualitative descriptive study, based on a literature review, aims to analyze two key policies: the Decree of the Director General of Islamic Education No. 1262 of 2024 concerning Technical Guidelines for Child-Friendly Care in Islamic Boarding Schools, and the Minister of Religious Affairs Regulation No. 73 of 2022 on the Prevention and Handling of Sexual Violence in Educational Institutions under the Ministry of Religious Affairs. Data sources include articles, journals, books, and other relevant literature on violence in pesantren environments. The findings reveal that, despite the issuance of these regulatory policies, cases of violence in pesantren persist. The study underscores the urgent need to strengthen and clarify evaluation and enforcement mechanisms at all institutional levels to effectively prevent and address such cases.